2013
DOI: 10.1038/ncomms2576
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a material gradient in the adhesive tarsal setae of the ladybird beetle Coccinella septempunctata

Abstract: For an insect to be able to efficiently attach to surfaces, the adhesive pads on the distal parts of its legs must establish large contact areas. In case of hairy adhesive pads this requires flexibility of the contact-forming bristles, called adhesive tarsal setae. However, too flexible setae would have a low mechanical stability resulting in a decreased attachment ability of the pads. Here we show that the adhesive tarsal setae of the ladybird beetle Coccinella septempunctata feature pronounced gradients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
245
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(262 citation statements)
references
References 50 publications
(55 reference statements)
15
245
1
1
Order By: Relevance
“…Each seta tip is only a few micrometres wide and only few studies have attempted to design elaborate strategies to measure in vivo their mechanical and adhesive properties [8][9][10][11]. Nanoindentation measurements on the setae of lady beetle Coccinella septempunctata revealed a large difference in Young's modulus between the tip (1.2 MPa) and the stalk (6.8 GPa) [12]. These values are consistent with the ability of Gastrophysa viridula seta tips to accommodate surface roughness [13].…”
Section: Introductionsupporting
confidence: 58%
“…Each seta tip is only a few micrometres wide and only few studies have attempted to design elaborate strategies to measure in vivo their mechanical and adhesive properties [8][9][10][11]. Nanoindentation measurements on the setae of lady beetle Coccinella septempunctata revealed a large difference in Young's modulus between the tip (1.2 MPa) and the stalk (6.8 GPa) [12]. These values are consistent with the ability of Gastrophysa viridula seta tips to accommodate surface roughness [13].…”
Section: Introductionsupporting
confidence: 58%
“…Gradients of different origin in biological materials are known, but rarely with nanopattern features (33)(34)(35). For the observed gradient in the Morpho scales, there are several potential origins: (i) variations in spatial patterning in the scale epicuticle during scale formation; such patterning may arise from stresses from elastic buckling of the outer epicuticle to produce the ridge lamellae (36), or may arise from propagating molecular signaling to provide local orientation and polarity (37); (ii) variable subsurface contributions to van der Waals and other surface interactions of the same surface molecules (15,38); (iii) active deposition of various molecules by the epidermal cell (35); and (iv) preferential covering of the cuticle with mobile lipid layers (39) that could accumulate in the narrow spaces on the ridge.…”
Section: Discussionmentioning
confidence: 99%
“…This review focuses on inorganic materials, such as metals, semiconductors, ceramics and the interfaces in between, but just as a vision for future development of interfaces, the invention of a new adhesive material -super-gecko‖ is reviewed. Bio-inspired research found first the reason for [1], then the mechanism of setae [2], and finally it OPEN ACCESS could be mimicked as synthetic composites [3] with further improvement [4]. Reversible interfacial bonds are considered to be realized by van-der-Waals bonds.…”
Section: Introductionmentioning
confidence: 99%